Financial inclusion drivers, motivations, and barriers: Evidence from Ethiopia - Workineh Ayenew Mossie (Cogent Business & Management)
Financial inclusion is a cornerstone for economic growth. However, the area is not well explored in the developing world. Therefore, this paper is motivated to examine the drivers, barriers and motivations associated with financial inclusion in Ethiopia. We used formal accounts, formal savings, and formal credits as financial inclusion indicators and applied a probit regression model using data from the World Bank’s 2017 Findex database. The result of the study showed that the determinants, barriers, saving and credit motivations are different across individual characteristics. Involuntary exclusion (such as distance to financial services and lack of documentation) and voluntary exclusion (lack of funds, a family member has an account,) are significant barriers to formal account ownership. The study also found that the motives for using financial accounts for saving and lending differ among people with different sociodemographic characteristics. To promote financial inclusion, the author suggests that the concerned body take actions toward social inclusion (the poor, women and the youngst) and improve financial education . To enhance further adoption and expansion of financial technologies such as mobile banking and mobile money, there should be mechanisms to ensure the accessibility and usage of financial services.